Femoral arteriovenous extracorporeal carbon dioxide elimination using low blood flow. - Young, J; Dorrington, K; Blake, G; Ryder, W (1992)
BACKGROUND AND METHODS: Conventional extracorporeal CO2 removal systems require blood flow rates of 1 to 2.5 L/min in the extracorporeal circuit. We hypothesized that standard hemofiltration equipment can be combined with a high-performance extracorporeal lung to achieve high rates of CO2 removal at lower blood flow rates. To test this hypothesis, we performed experiments on nine sheep to examine the extent to which CO2 elimination can be achieved at blood flow rates less than 600 mL/min using a 5-m2 hollow fiber membrane lung with countercurrent gas flow, combined with a hemofiltration blood pump, and connected to femoral arterial and venous hemodialysis catheters. RESULTS: CO2 eliminations of 130 to 180 mL/min at standard temperature and pressure were achieved with blood flow rates in the range 470 to 600 mL/min. With a pumpless artery-to-vein shunt, up to 90 mL/min of CO2 at standard temperature and pressure was eliminated. However, in this mode, the resistance of the access catheters and tubing was the main factor limiting CO2 elimination. CONCLUSIONS: Standard hemofiltration equipment may be combined with a hollow fiber membrane lung to remove the equivalent of a high proportion of the basal metabolic CO2 production of an adult human at low blood flow rates. Use of this technology would bring extracorporeal CO2 removal within the budget and capability of more ICUs.